Non-parametric genetic prediction of complex traits with latent Dirichlet process regression models - Ping Zeng (Nature Portfolio, 2017)
Genetic prediction of complex traits with polygenic architecture has wide application from animal breeding to disease prevention. Here, Zeng and Zhou develop a non-parametric genetic prediction method based on latent Dirichlet Process regression models.